Explaining physics: an online test for self-assessment and instructor training. (30th November 2018) - Bartels, Hauke; Kulgemeyer, Christoph
Abstract: Explaining physics content in an understandable way has been described as a vital skill for physics teachers in schools and universities. Studies suggest that physics teacher trainees regard explanation as one of the hardest challenges of their profession, and many scholars argue that explanation should be a part of physics teacher education. This paper presents an online test instrument for physics explanatory skills. It has been developed for diagnostic purposes and can be used—among other things—for teacher training and self-assessment (available via a weblink). The test takes about 45 min and calculates a score for explanatory skills as well as an indicator for underlying reasoning strategies. The individual results are compared with average scores from a study with physicists involved in science communication and physics teacher trainees. This comparison allows an estimation of the participants' skill to explain physics content successfully and gives hints on how to improve. The test consists of video scenes which show a teacher in the attempt to explain a physics phenomenon to a student. When the student asks a question, the video stops and the participant has to decide how to continue. Afterwards, he or she is asked to reason the choice made. The dialogue continues with the next video scene. In this paper, we summarise findings on how a science teaching explanation should be provided and discuss how the test instrument covers these aspects. Findings from a study with N = 154 participants are briefly discussed to show evidence for the validity of the instrument. Finally, possible uses of the test are proposed, including (self-)assessment, physics teacher education, and evaluation of training programs for all those who are involved in explaining physics.